In vitro interactions of coumarins with iron - Mladenka, Premysl; Macáková, Katerina; Zatloukalová, Libuse; Reháková, Zuzana; Singh, Brajendra K; Prasad, Ashok K; Parmar, Virinder S; Jahodár, Ludek; Hrdina, Radomír; Saso, Luciano (Biochimie, 2010)
Coumarins are a large group of natural substances with diverse pharmacological properties that may predetermine some of them for the prevention and/or treatment of cardiovascular diseases and also other pathologies. Free iron participates in the production of reactive oxygen species (ROS) and plays an important role in the pathogenesis of cardiovascular diseases. Therefore, chelation of iron may attenuate some ROS consequences, but on the other hand, reduction of ferric ions to ferrous ones is unfavourable and leads to intensification of ROS production. In this study, we have examined the interaction of iron with coumarins which has been rarely analyzed. A series of naturally occurring and chemically synthesized 4-methylcoumarins were analyzed for their ferrous and total iron-chelating properties and compared with standard iron chelator deferoxamine. The iron chelation activity was assessed by a simple spectrophotometric approach based on the specific indicator for ferrous ions--ferrozine. The methodology was also extended for the measurement of total iron. Among the tested coumarins, ortho-dihydroxyderivatives were the most potent iron chelators and 7,8-dihydroxy-4-methylcoumarin even reached the efficiency of deferoxamine in neutral pH. However, these ortho-dihydroxycoumarins did not bind iron firmly in acidic conditions (e.g., in acute myocardial infarction) and, moreover, they reduced ferric ions that could lead to intensification of the Fenton chemistry. Other tested coumarins did not substantially chelate iron with the exception of ortho-diacetoxycoumarins. Conclusively, the use of iron-chelating coumarins in acidic conditions may be disadvantageous in contrast to neutral conditions.
Keywords: kumariny; Coumarins; Antioxidants; Ferrozine; koncentrace vodíkových iontů; ferrozin; železo; Iron; Molecular Structure; molekulární struktura; antioxidancia; Iron Chelating Agents; chelátory železa; Hydrogen-Ion Concentration